2018
DOI: 10.1097/imi.0000000000000463
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Patient-Specific Three-Dimensional Simulation of Mitral Repair

Abstract: Objective Planned mitral repair strategies are generally established from preoperative echocardiography; however, specific details of the repair are often determined intraoperatively. We propose that three-dimensional printed, patient-specific, dynamic mitral valve models may help surgeons plan and trial all the details of a specific patient's mitral repair preoperatively. Methods Using preoperative echoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…3 Functional 3D models and their coupling with a mock circulatory system. Images in the figure are from the literature [72][73][74] same two materials to create aortic valve complexes, and confirmed their feasibility for ultrasound imaging. Biglino et al [72] made a blood vessel model using TangoPlus, and demonstrated its suitability for fabricating arteries, although its mechanical properties might not be suitable for modeling softer blood vessels.…”
Section: Flexible Materials For 3d Cardiovascular Modelsmentioning
confidence: 57%
See 3 more Smart Citations
“…3 Functional 3D models and their coupling with a mock circulatory system. Images in the figure are from the literature [72][73][74] same two materials to create aortic valve complexes, and confirmed their feasibility for ultrasound imaging. Biglino et al [72] made a blood vessel model using TangoPlus, and demonstrated its suitability for fabricating arteries, although its mechanical properties might not be suitable for modeling softer blood vessels.…”
Section: Flexible Materials For 3d Cardiovascular Modelsmentioning
confidence: 57%
“…Scanlan et al [73] compared 3D models of the tricuspid valve obtained by the two methods, and reported that both closely replicated the patient's anatomy, while the silicone model was better at simulating the texture of cutting and stitching. Based on the ultrasound images, a mitral valve prolapse model created by Olivia et al [74] using Echoflex 00-30 also had good fidelity to the preoperative three-dimensional echocardiogram. Such materials are promising for the production of low-cost functional 3D cardiovascular models.…”
Section: Flexible Materials For 3d Cardiovascular Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent developments in the assessment of MR with potential future value include (I) the 'average pixel intensity' (API) method (92), a novel digital quantification of the CW pixel intensity in grading MR severity; (II) 4D-flow CMR (93), which allows correction for MV motion; (III) real-time 3D TOE-based 4-dimensional MV models (94), which allow excellent morphological visualization and a comprehensive quantitative analysis of MV annulus and leaflets during the entire cardiac cycle; and (IV) 3D printing of MV (95,96), where the anatomy of a patient-specific MV can be accurately modeled to improve pre-operative planning of complex surgical interventions.…”
Section: Future Directionsmentioning
confidence: 99%